2020
DOI: 10.1007/s11695-020-04973-8
|View full text |Cite
|
Sign up to set email alerts
|

Transversus Abdominis Plane Block Appears to Be Effective and Safe as a Part of Multimodal Analgesia in Bariatric Surgery: a Meta-analysis and Systematic Review of Randomized Controlled Trials

Abstract: Purpose Pain after bariatric surgery can prolong recovery. This patient group is highly susceptible to opioid-related side effects. Enhanced Recovery After Surgery guidelines strongly recommend the administration of multimodal medications to reduce narcotic consumption. However, the role of ultrasound-guided transversus abdominis plane (USG-TAP) block in multimodal analgesia of weight loss surgeries remains controversial. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Epidural analgesia for postoperative pain is effective but is not required in laparoscopic surgery. Ultrasound-guided transversus abdominis plane block can decrease pain scores and opioid requirement, and improve ambulation after bariatric surgery [ 134 ]. Infiltration of bupivacaine 0.5% before incision results in a reduction in opioid consumption and postoperative pain [ 135 ].…”
Section: Results: Evidence Base and Recommendationsmentioning
confidence: 99%
“…Epidural analgesia for postoperative pain is effective but is not required in laparoscopic surgery. Ultrasound-guided transversus abdominis plane block can decrease pain scores and opioid requirement, and improve ambulation after bariatric surgery [ 134 ]. Infiltration of bupivacaine 0.5% before incision results in a reduction in opioid consumption and postoperative pain [ 135 ].…”
Section: Results: Evidence Base and Recommendationsmentioning
confidence: 99%
“…The majority (83 %) of the simulation-based TAP block learning group passed the assessment compared to only (33 %) of the video-based TAP block learning group, showcasing that simulation-based learning can significantly impact learner capabilities ( Table 2 ). Similarly, several studies have assessed simulation-based learning and found it compelling due to significantly improving the trainee's comfort level and confidence/success, which further supports the efficacy of simulation-based surgical education [ [34] , [35] , [36] ].…”
Section: Discussionmentioning
confidence: 74%
“…UGSA-TAP block is a viable concept. The increasing popularity of the UGSA-TAP block can be attributed to the confidence of the trainee surgeons in performing the fascial plane block, which is well known to be safe either performed by an anesthesia or non-anesthesia provider [ 36 ]. Our study recommends that education and training on TAP block are necessary for surgeons interested in performing the UGSA-TAP block.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain may affect patients’ motivation to engage in rehabilitation exercises. 35 , 36 Meanwhile, pain intensity is aggravated by rehabilitation, which may limit the patient’s participation. 37 A previous study have shown that lack of rehabilitation is an independent risk factor for stiff elbow.…”
Section: Discussionmentioning
confidence: 99%